A flexible control study of variable speed limit in connected vehicle systems. (2015) - Pu, Lu; Xu, Xiaowei; He, Han; Zhou, Hanqing; Qiu, Zhijun; Hu, Yu
Traffic congestion has already been a distinctly serious problem in both developed and developing countries. Among the proposed methods to solve the traffic congestion problem, variable speed limit (VSL) is considered as one of the most promising methods. But to the traditional VSL, the speed limit sign and the control distance is fixed, which makes VSL lack deployment and control flexibility. Whereas, in connected vehicle (CV), which is a crossing field of intelligent transportation systems (ITS) and internet of things (IoT), control and deployment flexibility can both be achieved. Furthermore, a big data environment is formed in CV to solve the traffic problems. In this paper, connect vehicle-based variable speed limit (CV-VSL) is proposed, and a simulation platform SimIVC is used to study the influence of control distance. The results show that the improvement of traffic performance increases 0.72% when the control distance is 270 metres than that of 250 metres, which means that the traffic performance can be further improved by CV-VSL.